Avaliação da relação de ansiedade, alterações de memória e concentração em pacientes com síndrome pós-covid 19 - PELAES, Larissa Andrade (2024)
Introduction: post-COVID-19 syndrome is a condition that remains poorly understood currently, and among its most prevalent symptoms are neuropsychiatric alterations such as memory deficits, concentration impairments and anxiety. Objective: the aim of this study was to assess the relationships between memory impairment and anxiety in patients with post-COVID-19 syndrome, describing the symptom prevalence, associated risk factors, and comparing demographic and clinical characteristics of the patients. Methods: this is a cross-sectional study with an analytical-explanatory approach. Clinical follow-up was conducted from 2022 to 2023 on patients treated at the Tropical Medicine Center, affiliated with the Federal University of Pará, who had recovered from SARS-CoV-2 infection. The Mini-Mental State Examination (MMSE), the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) word list, and the Hamilton Anxiety Scale were used. Fisher's exact test and chi-square test were used for qualitative variable analysis, and the Student's t-test or Mann-Whitney test was used for quantitative variable comparison, with significance set at p<0.05. Simple Logistic Regression was performed to identify variables independently associated with cognitive deficits and with the Kappa test. Results: data from 81 patients were analyzed, with a mean age of 54.65 (±12.23) years, of which 58 had some form of comorbidity. It was identified that 62 (76,54%) had complaints of memory and concentration deficits. When the CERAD was performed, it was observed that only 10 (12.34%) showed alterations in immediate and/or delayed memory. According to the Hamilton scale, 58 (71.60%) had a considerable degree of anxiety. There was no relationship between the degree of anxiety and the memory alteration identified by CERAD and/or MMSE. A relationship between memory deficit complaints and the degree of anxiety was observed. There was a significant relationship between memory impairment and the presence of comorbidities, including systemic arterial hypertension (odds 5.47 and p-value 0.04), alteration in the glycemic profile (odds 4.59 and p-value 0.039) and obesity (odds 7.18 and p-value 0.022) had a significant p-value. Conclusion: the research showed that, in the context of the post-covid syndrome, the memory alteration complaint is common in anxious patients, however, 87,66% of the sample did not attest memory alteration. When memory impairment was associated with comorbidities, an unfavorable impact on the process of neurological recovery of cognitive functions was demonstrated. Furthermore, no significant relationship was observed between age and education in the studied group with such alterations.